Effects of dietary linseed-based N-3 fatty acids on growth performance, fatty acid profile, meat quality and rumen mucosa morphology of crossbred boer goats underintensive conditions - Abdelmaged, Kamaleldin Abuelfatah Mohamed (2014)
Ruminant meats are characterized by a high ratio of saturated fatty acids (SFA), a low ratio of polyunsaturated fatty acids (PUFA), and a high ratio of PUFA n-6: n-3, which have been associated with modern life diseases. Different from beef and sheep, the information about the effect of the feeding dietary regime, in general, and n-3 PUFA, in particular, on fatty acid (FA) profiles of goat's edible tissues is scarce. This study was conducted to increase n-3 PUFA content and conjugated linoleic acids (CLA) in goat meat through feeding different levels of whole linseed, as a source of <1-linolenic acid (ALA) n-3 PUFA, and investigate its effects on the growth performance, carcass characteristics, meat quality, and changes in rumen fermentation parameters and mucosal morphology. Twenty-four, 5-month old crossbred Boer bucks with a mean live weight of 14.23 i 0.33 kg were assigned equally (n=8) into three isocaloric and isonitrogenous treatment diets that differed in the level of linseed. The diets L0, L10 or L20 contained 0%, 10% and 20% (W/W) whole linseed, respectively. The animals were slaughtered after a feeding period of 110 days. Upon slaughter, samples from liquor and tissues of the rumen were collected for analysis. The carcasses were dissected and samples from three muscles, longissimus dorsi (LD), supraspinatus (SS) and semitendinosus (ST), and internal and subcutaneous fats were taken for FA analyses. Subsamples from the muscles were aged for 1 or 7 days at 1- 4 °C before subjecting to the meat quality and lipid oxidation analyses. The results revealed that the inclusion of linseed increased the proportion of ALA by 5.7, 6.75 and 7.0 fold, and 12.52, 10.25 and 11.67 fold in the LD, SS and ST muscles, for L10 and L20, respectively. The total n-3 PUFA was increased by 3.4, 3.2 and 3.6 fold, and 4.73, 4.14 and 5.5 fold in the LD, SS and ST muscles, for L10 and L20, respectively. In adipose tissues, the increment in ALA was 3.07 and 6.92 fold; and 3.00 and 7.54 folds in the subcutaneous and perirenal fats for L10 and L20, respectively, compared to L0. The proportions of beneficial long chain n-3 PUFA ecosapentaenoic, docosapentaenoic, and docosahexaenoic in the muscles were Significantly increased; nevertheless, these FA were not detected in the adipose tissues. The PUFA n-6:n-3 ratio decreased from 8.86, 7.55 and 6.65 in LD, SS and ST, respectively for L0 to 1.68, 1.87 and 2.0; and 1.16, 1.8 and 1.32 for L10 and L20, respectively. There was also a significant decrease in the SFA in all tissues except for the LD muscle and perirenal. The CLA increased in all tissues except for the LD muscle. At 20% inclusion (L20), the PUFA:SFA ratio was significantly higher in all studied tissues compared to the control gI'Ol1p. The final weight, total weight gain, and apparent digestibility were not affected by the treatments (P >0.05). However, the goats fed the L20 diet had lower (P < 0.05) feed intake (669.30 g/ day) compared to L0 (705.21 g/ day) or L10 (698.51 g/ day). The gain: feed ratio (G:F) was higher (P< 0.05) in L20 compared to other treatment groups. The internal fat weight was heavier (P< 0.05) in L20 (550.57 g) compared to L10 (373.00 g), while in L0 was in between (469.40 g) with no difference (P>0.05). The percentage of lean was better (P< 0.05) in L10 (67.82%) compared to L0 (65.25%) or L20 (64.78%). There was no effect (P>0.05) on cooking loss, shear force or color for the different muscles at the 1-day postmortem aging time. However, at the 7-day aging time the color of all the muscles was significantly affected by the treatment diets. Subjectively, no differences were detected between the goat meat enriched in n-3 PUFA (L10 and L20) and the control (L0) in color, flavor or aroma. However, the tenderness, juiciness and overall acceptability of L20 meat were rated better than those of L0 and L10. The thiobarbituric acid reactive substances (TBARS) value in all muscles was increased with increasing the contents of n-3 PUFA and postmortem aging time. The lowest TBARS values were constantly shown by L0, while the highest values were indicated by the samples of L20 for the various muscles and aging times. The rumen digesta of goat fed linseed (L10 and L20) had a significantly higher proportion of stearic acid, vaccenic, C18:2 trans-10, cis-12 CLA, and ALA compared to L0. The palmatic was significantly lower in L0 and L20 compared to L0. However, no significant effect was observed in the proportion of oleic, linoleic (LA), CLA isomer C18:2 cis-9, trans-11, and arachidonic. The pH of the rumen liquor and concentration of total volatile fatty acids (VFA) were not affected by the treatments (P<0.05). However, L10 and L20 had a higher (P<0.05) molar proportion of acetate, and lower (P<0.05) molar proportion of butyrate and valerate. compared to L0. Both inclusion levels of linseed in the diet (L10 and L20) significantly reduced the total bacteria, methanogens, and protozoa, in the rumen liquor compared to the L0. The effect of the dietary treatments on cellulolytic bacteria, varied between the individual species. Both inclusion levels of linseed resulted in a significant decrease in the population of the Fibrobucier succinogenes, and Rumunococus ﬂavefuciens compared to L0, with no significant difference between the groups fed linseed diets (L10 and L20). Nevertheless, the population of Rumunococus ulbus was not affected by the different dietary treatments. The inclusion of linseed in diets also induced some changes in rumen mucosal morphology. The animals fed linseed (L10 and L20) had longer papillae in the atrium ruminis, dorsal rumen wall, and caudoventral blind sac regions compared to the control (L0) and it was only significantly higher in the ventral rumen wall for L20. In addition, feeding linseed significantly increased the papillae width in the caudoventral blind sac and the ventral rumen wall regions. The papillae area was greater in the most studied regions of the rumen (dorsal rumen wall, caudoventral blind sac, and ventral rumen wall) of L10 and L20 compared to L0. It is concluded that both inclusion levels (10% and 20%) of linseed as a source of n-3 PUFA in goats diets resulted in producing meat highly enriched with n-3 PUFA with desirable n-6:n~3 ratio without any adverse effect on the growth performance, carcass characteristics or meat quality. The inclusion of linseed at 10% (w/w) resulted in improving the goat carcass characteristics, while at 20% (w/w) resulted in improving G:F ratio and the eating quality of goat meat. Moreover, the inclusion of linseed decreased the rumen microorganism involved in methanogenesis, and increased the surface area of the rumen papillae.